Die implikasies van ’n konsekwent probleem-historiese metode van wysgerige historiografie vir geslagtelike verskille en verhoudings - Walt, Barend Johannes van der (Koers, 2014)
The implications of a consistent problem-historical method of philosophical historiography for gender distinctions and relations. Reconnoitring the possible implications of the consistent problem-historical method of Dirk H.Th. Vollenhoven (1892–1978) to attain more clarity on the issue of gender and gender relations is the main aim of this investigation. In passing, it also indicates how the results obtained by this Christian philosopher’s careful analysis of Western ontologies and anthropologies may alleviate the deficiencies in the otherwise ground-breaking study of sister Prudence Allen. Allen’s study was discussed in a previous article in this journal. The introductory section explains how Vollenhoven himself viewed the difference and relation between God, his laws and his creation. The next section discusses the main contours of his historiography of philosophy, viz. his division of the history of philosophy intothree main periods (pre-synthetic, synthetic and anti-synthetic), a diversity of normative time-currents and three basic cosmological problems (consistency versus change, unity versus diversity and universal versus individual). From the great number of anthropologies, the third section selects a few examples to illustrate their possible implications for the problems related to sexuality and gender. The conclusion tries to pinpoint Vollenhoven’s own anthropology in order to ascertain why he, in spite of his thorough and profound exposure of the ontological and anthropological foundations of Western thinking, did not more explicitly express himself about their implications for gender issues.